TLR4 and TLR9 Polymorphisms Effect on Inflammatory Response in End-Stage Renal Disease Patients. (September 2014) - Santos-Martins, M.; Sameiro-Faria, M.; Ribeiro, S.; Rocha-Pereira, P.; Nascimento, H.; Reis, F.; Miranda, V.; Quintanilha, A.; Belo, L.; Beirão, I.; Santos-Silva, A.; Bronze-Da-Rocha, E.; et al.
Toll-like receptors (TLRs) play a key role in the response of innate and adaptive immune system to microbial and endogenous ligands. Inflammation is a common feature in end-stage renal disease (ESRD) patients; however, the mechanisms/factors triggering the inflammatory process are still poorly clarified. Our aim was to analyze the impact of the c.-1486T>C and c.896A>G polymorphisms in TLR9 and TLR4 genes, respectively, on the inflammatory response of ESRD patients. Clinical and laboratory evaluation was carried out on 184 ESRD patients. Polymerase chain reaction followed by restriction fragmens length polymorphisms (PCR-RFLP) was employed for genotyping of TLR-4 c.896A>G and TLR-9 c.-1486T>C polymorphisms. The prevalence of AA and AG of TLR4 c.896A>G polymorphism in ESRD patients was 97.8% and 2.2%, respectively. None of the individuals showed a homozygous TLR4 polymorphism. Concerning the TLR9 c.-1486T>C polymorphism, we found that ESRD patients showed a prevalence of TC and CC genotypes of 57.1% and 20.6%, respectively. We found that the heterozygous patients for the TLR4 c.896A>G polymorphism presented an increased level in lymphocyte count, a decrease in neutrophil/lymphocyte ratio and in serum levels of hepcidin. Regarding the TLR9 c.-1486T>C polymorphism, we found that it is associated with decreased white blood cell and neutrophil counts, ferritin and CRP serum levels, and with an increase in serum levels of creatinine. Our data suggest that the presence of the studied polymorphisms is associated with a decreased inflammatory response in ESRD patients under hemodialysis, and, thus its presence might have beneficial effects in ESRD patients. Moreover, our data provide new insights in the role of TLR polymorphisms in renal disease, which might have impact in the near future for the development of innovative therapies.